Measurements of W and Z boson production in pp collisions at s√=5.02 TeV with the ATLAS detectors - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Britzger, Daniel; Chouridou, Sofia; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; et al. (The European physical journal. C, Particles and fields, 2019)
Measurements of fiducial integrated and differential cross sections for inclusive W+W+W^+, W−W−W^- and Z boson production are reported. They are based on 25.0±0.5pb−125.0±0.5pb−125.0 ± 0.5\; pb^{-1} of pp collision data at s√=5.02s=5.02\sqrt{s} = 5.02 TeV collected with the ATLAS detector at the CERN Large Hadron Collider. Electron and muon decay channels are analysed, and the combined W+W+W^+, W−W−W^- and Z integrated cross sections are found to be σW+=2266±9 (stat)±29 (syst)±43 (lumi)σW+=2266±9 (stat)±29 (syst)±43 (lumi)σ _{W^+}= 2266 ± 9~\text {(stat)} ± 29~\text {(syst)} ± 43~\text {(lumi)} pb, σW−=1401±7 (stat)±18 (syst)±27 (lumi)σW−=1401±7 (stat)±18 (syst)±27 (lumi)σ _{W^-}= 1401 ± 7~\text {(stat)} ± 18~\text {(syst)} ± 27~\text {(lumi)} pb, and σZ=374.5±3.4 (stat)±3.6 (syst)±7.0 (lumi)σZ=374.5±3.4 (stat)±3.6 (syst)±7.0 (lumi)σ _Z= 374.5 ± 3.4~\text {(stat)} ± 3.6~\text {(syst)} ± 7.0~\text {(lumi)} pb, in good agreement with next-to-next-to-leading-order QCD cross-section calculations. These measurements serve as references for Pb+Pb interactions at the LHC at sNN−−−√=5.02sNN=5.02\sqrt{s_{NN}}=5.02 TeV.
Gesehen am 04.12.2019
The ATLAS collaboration: M. Aaboud [und 2920 weitere Personen]
Im Titel ist 'pp' kursiv dargestellt